2021
DOI: 10.1182/blood.2020006198
|View full text |Cite
|
Sign up to set email alerts
|

Plasmin-mediated Cleavage of High Molecular Weight Kininogen Contributes to Acetaminophen-Induced Acute Liver Failure

Abstract: Acetaminophen (APAP)-induced liver injury is associated with activation of coagulation and fibrinolysis. In mice, both tissue factor-dependent thrombin generation and plasmin activity have been shown to promote liver injury after APAP overdose. However, the contribution of the contact and intrinsic coagulation pathways has not been investigated in this model. Mice deficient in individual factors of the contact (FXII and PK) or intrinsic coagulation (FXI) pathway were administered a hepatotoxic dose of 400 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…46 Henderson et al have recently found that plasmin-generated proteolytic fragments of high-molecular-weight kininogen induce the apoptotic death of endothelial cells and proinflammatory activation of leukocytes. 94 The degradation of ECM by plasmin results in the liberation of vessel permeability regulators, such as VEGF and TGF-β. 91 Plasmin has also been shown to activate protease-activated receptors (PAR), directly or through plasmin-activated MMP-1.…”
Section: Connections Between Plasmin Inhibition and Txa Effects Trans...mentioning
confidence: 99%
See 1 more Smart Citation
“…46 Henderson et al have recently found that plasmin-generated proteolytic fragments of high-molecular-weight kininogen induce the apoptotic death of endothelial cells and proinflammatory activation of leukocytes. 94 The degradation of ECM by plasmin results in the liberation of vessel permeability regulators, such as VEGF and TGF-β. 91 Plasmin has also been shown to activate protease-activated receptors (PAR), directly or through plasmin-activated MMP-1.…”
Section: Connections Between Plasmin Inhibition and Txa Effects Trans...mentioning
confidence: 99%
“…Thus, plasmin cleaves IL‐8 to a more potent form for granulocyte activation and cleaves CCL21 chemokine bound to ECM to generate a soluble chemotactic fragment 46 . Henderson et al have recently found that plasmin‐generated proteolytic fragments of high‐molecular‐weight kininogen induce the apoptotic death of endothelial cells and proinflammatory activation of leukocytes 94 . The degradation of ECM by plasmin results in the liberation of vessel permeability regulators, such as VEGF and TGF‐β 91 .…”
Section: Connections Between Plasmin Inhibition and Txa Effects Trans...mentioning
confidence: 99%
“…Infection with CoV-2 By cleaving the spike proteins of the SARS-CoV-2 virus, plasmin increases its virulence and infectivity. [6].…”
Section: Resultsmentioning
confidence: 99%
“…41 In contrast to FXII, HK has recently been shown to have a role in experimental liver inflammation. 42 Together the data reveal differential roles of contact system proteins in distinct inflammatory disease states. 43…”
Section: Targeting Factor XII In Allergy and Inflammationmentioning
confidence: 91%